The quality of Anadara granosa based on Cadmium metal test in the coastal area of Langsa in Aceh - Mawardi Mawardi; Tri Mustika Sarjani (Universitas Syiah Kuala, 2017)
Langsa is a coastal area with vast expanse area inhabited 0f mangrove. There are lives some animal species (shells, oyster, snails and various of fish). The objectives of present study was to evaluated accumulation of Cadmium metal on Anadara granosa in the coastal area of Langsa. A total of two sampling locations were determined using the purposive of random sampling. A total individual of Anadara granosa at every sampling location were colletcted, the organs were processed for Atomic Absorption Spectrophotometry (AAS). The result test showed that only at Alur Dua that accumulated Cadmium metal in Anadara granosa whereas at Kuala Langsa is not detected. Anova test showed that the sampling location significantly influenceon the Cadmium accumulation in Anadara granosa (P0,05). Kuala Langsa is not contaminated with Cadmium and the Anadara granosa should be consumed. The higher of Cadmium contaminated was recorded in Alur Dua and the Anadara granosa should not be consumed.